Rice SnRK protein kinase OsSAPK8 acts as a positive regulator in abiotic stress responses. (March 2020) - Zhong, Ruiling; Wang, Yuxia; Gai, Ruonan; Xi, Dandan; Mao, Chanjuan; Ming, Feng
Highlights: OsSAPK8 is activated by abiotic stresses, including cold, drought and high salt. OsSAPK8 is a positive regulator in freezing, drought and salt tolerance. Abiotic stress related genes are inhibited in OsSAPK8-defective mutants. Abstract: SnRK2 (sucrose non-fermenting 1-related protein kinases 2) protein kinase family involves in several abiotic stress response in plants. Although the regulatory mechanism of SnRK2 have been well demonstrated in Arabidopsis thaliana, their functions in rice are still largely unknown. Here, we report a SnRK2 family gene, OsSAPK8, can be strongly induced by abiotic stresses, including low-temperature, drought and high salt stress. The ossapk8 mutants showed lower tolerance to low-temperature, high salinity and drought stresses at the vegetative stages. Moreover, the expressions of marker genes for those abiotic stresses, e.g. OsDREB1, OsDREB2, OsNCED and OsRAB21, were downregulated in the ossapk8 mutants. We further confirmed that the yield was reduced in ossapk8 mutant lines compared with the wild type. Our results provide evidence for OsSAPK8 acting as a positive regulator in cold, drought, and salt stress responses.